2017
DOI: 10.1002/ldr.2824
|View full text |Cite
|
Sign up to set email alerts
|

Abandonment of traditional terraced landscape: A change detection approach (a case study in Costa Viola, Calabria, Italy)

Abstract: This paper presents the results of a change‐detection study of the historical agricultural terraced landscape in “Costa Viola” (Calabria, South Italy). During the last century, because of the loss of economic competitiveness, it has undergone progressive abandonment, followed by landscape degradation. Taking into consideration the very steep slopes of Costa Viola and the need to analyse with high precision the historical evolution of the terraced landscape, research methods were implemented coupling advanced g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…Earlier studies have quantified the loss of terraced agro-ecosystems in Italy over the past 50 years [19], presenting values close to 40% in Tuscany, central Italy [5,6], 33% in Liguria, northern Italy [69], and 85% in Calabria, southern Italy [27]. In this regard, our study has estimated land-use changes over both long and short time horizons in the identified TLS and proximal buffer area (terraces' contact areas) and the amount of abandoned terraces.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Earlier studies have quantified the loss of terraced agro-ecosystems in Italy over the past 50 years [19], presenting values close to 40% in Tuscany, central Italy [5,6], 33% in Liguria, northern Italy [69], and 85% in Calabria, southern Italy [27]. In this regard, our study has estimated land-use changes over both long and short time horizons in the identified TLS and proximal buffer area (terraces' contact areas) and the amount of abandoned terraces.…”
Section: Discussionmentioning
confidence: 53%
“…As a consequence of population aging, land abandonment has largely occurred in terraced landscapes determining biodiversity loss, soil erosion and land degradation [21,26,27]. Land abandonment may indirectly stimulate forest expansion in marginal areas, leading to increased wildfire frequency and intensity [18,28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the Italian rural landscapes the agricultural terraced ones-which characterize many regions such as Cinque Terre (Liguria) [32,33], Costa Viola (Calabria) [34][35][36][37], Costiera Amalfitana (Campania) [38], Valtellina (Lombardy) [39], Chianti (Tuscany) [32,40], Langhe (Piedmont) and so forth-can be seen as the most evident expression of the agricultural landscape as the result of a proper social construction. A construction that there appears as audacious and persevering, sometimes defined as "heroic," in all those cases when communities have intended to colonise for productive reasons harsh and steep lands, otherwise inhospitable, by clearing forests, reshaping land morphology, building retaining walls, stairs, irrigation channels and other functional artefacts [34][35][36][37]39] (Figure 2).…”
Section: Urban-rural Dialectics and Agricultural Landscape Changes Inmentioning
confidence: 99%
“…Particularly widespread in the Mediterranean area [6], terraces may be found in the Balearic Islands, in Spain, in France, along the Italian peninsula, in the Balkans and in Greece. In Italy, many authors studied terraced landscapes in the different and various contexts in the country [3,4,8,12,23,[26][27][28][29]. The original morphology has been modified (Figure 1) by terraced system that in some cases extended to the entire slope or even to high percentage of a catchment's surface, with challenging implications in water infiltration and superficial runoff [26,30,31].…”
Section: Introductionmentioning
confidence: 99%